Bhutanese teachers' attitudes towards inclusive education. Issue 5 (16th April 2021) - Dorji, Rinchen; Bailey, Jeff; Paterson, David; Graham, Lorraine; Miller, Judith
ABSTRACT: Inclusive education is a relatively new educational concept in Bhutan. Teachers play a critical role in the successful implementation of educational change. Investigating teachers' attitudes towards inclusion was conducted through an online survey. Respondents included 145 teachers (70 male and 75 female) from eight schools from across eight different districts in Bhutan, representing a return rate of 57%. Data were analysed using Rasch latent trait scaling techniques ( Proquest ) to determine the face validity of the survey. Case estimates from Rasch were incorporated into further analysis adopting the R statistical environment. Significant differences of attitude were detected based on gender (Pr(Chi) = 0.031); teacher qualifications (Pr(Chi) = 0.005); and experience of teaching children with special education needs (SEN) (Pr(Chi) = 0.018). The slightly positive attitude towards inclusion, measured by a 38-item questionnaire on a six-point scale, showed a mean average score of 3.965. Teachers' satisfaction of teaching children with SEN was positive (73%). The study also revealed the need for safer playgrounds, accessible toilets, less crowded classrooms, and greater education for teachers and support staff. These findings inform future policies and advancement of inclusive education in Bhutanese schools.